Wykorzystanie wybranych koncepcji rachunkowości zarządczej we współczesnych zintegrowanych systemach informatycznych rachunkowości - Kostrzewa, Tomasz (Selected Conceptions of Management Accounting Used in Contemporary Integrated Information Systems, 2005)
Ability to apply instruments in the field of management accounting are required from managers these days. Currently in complicated management conditions only support of integrated information system can contribute to keeping market position, or even increase efficiency of company function. The aim of the paper is to outline selected conceptions of managerial accounting used in environment of integrated information systems of accounting. The paper contains the general analysis of individual solutions with emphasis on the practical dimension for company management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 203-212